LEVEL OF FINANCIAL LITERACY REVIEWED VARIOUS FACTORS ON ECONOMIC STUDENTS - Maria Widyastuti; Lilik Indrawati; Penta Paula (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to analyze the level of financial literacy of students of the Faculty of Economics in terms of several factors, these factors are: gender, age, batch, program, grade index, dwelling, status, receipts, expenses, ownership account, education level of parents and income level of parents. The population in this study was undergraduate students, Accounting and Management study program, Faculty of Economics in East Surabaya who were active in the 2016-2020 batch. The method used was survey research using online questionnaires. The results showed that the level of student financial literacy in terms of several factors was still low. Keywords: literacy, finance, students